The influence of celebrity endorsement towards buying decision using online advertisement / Noryusnita Ramli ... [et al.] - Ramli, Noryusnita; Abd Latif, Zulkifli; Ismail, Siti Nasarah; Mohd Shukri, Nur Alyani; Mohd Alhadi, Mohd Shazreeq (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
A lot of brands use celebrity endorsement as a way to get people to pay attention to their marketing messages. Advertisers are willing to pay a lot of money to get the endorsements of these celebrities because they are the personal and social favourites most likely to influence consumers' buying decisions and lifestyles. The purpose of this study is to find out how celebrities are used to market to postgraduate students, how postgraduate students decide what to buy, and how the use of celebrities and buying decisions are linked. To do this, a quantitative survey was sent out to 170 postgraduate students by using a non-probability sampling. Findings show that using celebrity endorsement as a marketing strategy has a big effect on postgraduate students' buying decisions. Correlation coefficient analysis is used to identify the relationship between attractive, trustworthy, expertise, and congruence towards buying decisions. The takeaway from this study is that brands should not just choose celebrities based on how they look. Instead, they should use a strategy to choose the right celebrities to represent their brands.